Аналіз методів визначення раціональних типорозмірів шин для підвищення технічного рівня транспортних засобів подвійного призначення за рахунок зниження питомого тиску на ґрунт - Ребров, Олексій Юрійович; Петренко, Олексій Геннадійович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У статті проаналізовано сучасні методи визначення раціональних типорозмірів шин для підвищення технічного рівня транспортних засобів подвійного призначення за рахунок зниження питомого тиску на ґрунт. Обґрунтовано доцільність застосування шин із пониженим тиском у системах регулювання тиску, що забезпечують адаптацію транспортних засобів до різних умов експлуатації. Проведений аналіз застосування сучасних технічних рішень і інновацій у шинній галузі, спрямованих на підвищення прохідності, зменшення ущільнення ґрунту та підвищення ефективності використання машинно-тракторних агрегатів у цивільному та оборонному секторах.

The article analyzes modern methods for determining rational tire sizes aimed at improving the technical performance of dual-purpose vehicles through the reduction of specific ground pressure. The feasibility of using low-pressure tires equipped with automatic pressure control systems is substantiated to ensure adaptability to different operating conditions. The research examines recent technological innovations in the tire industry, including the implementation of IF and VF tire technologies, and their impact on traction efficiency, soil protection, and energy consumption. Experimental data demonstrate that properly selected tire dimensions and pressure adjustment significantly enhance vehicle passability, reduce fuel usage, and minimize soil compaction. The obtained results can be applied in the modernization of agricultural and military vehicles to improve operational efficiency and environmental sustainability.
Analysis of methods for determining optimal tire sizes to Improve the technical level of dual-purpose vehicles by reducing specific ground pressure
Keywords: колісний трактор; ґрунт; понижений тиск; шини; транспорт подвійного призначення; wheeled tractor; soil; low pressure; tire; dual-purpose vehicle